Operational Monitoring of Trace Gases over the Mediterranean Sea - Giuseppe Grieco; Guido Masiello; Carmine Serio (Advances in Meteorology)
This paper describes the operational implementation of the processor φ-IASI over the Mediterranean sea. The φ-IASI model implements two physically based inversion algorithms for the sequential retrieval of (a) the thermodynamic state of the atmosphere and (b) the tropospheric content of CO, CO2, CH4, and N2O from hyperspectral radiance observations of the Infrared Atmospheric Sounding Interferometer (IASI). The retrieval algorithm for trace gases exploits the concept of partially scanned interferogram technique, which is a tool mostly suited for Fourier transform spectrometers in the infrared. Minor and trace gases retrievals for July 2010 are presented and compared to in situ observations from five Mediterranean, permanent, stations of the Global Atmospheric Watch (GAW) network. The comparison evidences a good general consistency between satellite and in situ observations. IASI retrievals show a marked southeastern gradient, which is shown to be consistent with the general tropospheric circulation over the Mediterranean basin. These patterns are barely seen from in situ observations, a fact which stresses the importance of satellite (trace gases) data assimilation to improve the performance and quality of trace gases transport models.